Arte e trabalho em São Luís do Maranhão: perspectivas e impressões de atores e atrizes sobre a atividade teatral. - SILVA, Rodrigo França (2018)
The present investigation aims to analyse the perspectives and impressions of actors and actresses on art and work in São Luís (Maranhão), as to their activities in the theater field. It proposes to discuss such human productive activity from the angle of dialogue between different knowledge areas, such as art, history and sociology, taking into account the interdisciplinary foundation of this investigation. Were considered the experiences from six actors in three theater productions, namely: “Pão com Ovo”, from Santa Ignorância Art Co.; “Velhos Caem do Céu como Canivetes”, from Pequena Companhia de Teatro; “João do Vale - O Musical”, a production from Maranhão’s Culture and Tourism State Department. Taking into account the work conditions and the perspectives and impressions from the actors and actresses who were interviewed, this paper aims to understand the social dimension that theatrical art has and which meanings it acquires on the perspective of culture, drawing a historical and theoretical panorama regarding the meanings of the words “work” and “artist”, on the context of Brazilian’s and São Luis’ theater, also aiming to consider sociological concepts that directly affects the discussion on the actor’s work.